Are more resources always the answer? A supply and demand analysis for public health services in Brazilian municipalities - Fabiana Rocha; Janete Duarte; Plínio Portela de Oliveira; Luis Felipe Vital Nunes Pereira; Sérgio Ricardo de Brito Gadelha (EconomiA, 2017)
The aim of this paper is to determine whether it is necessary to increase available resources to local governments or if better use of these funds is sufficient. The paper contributes to the literature by looking both at the supply and demand for public health services. If the demand is estimated correctly, one can compare its expected value to actual health expenditures. Even if actual expenditures are lower than the estimated demand, it is not certain that additional spending is necessary. If the efficiency scores (supply side) indicate that local governments can simply “save” resources to make up for the difference, then it is possible to reduce (or bring to zero) new resources only by requiring local governments to efficiently manage their expenditures. Since municipalities in Brazil are very heterogeneous, we estimate their efficiency using the metafrontier approach (O'Donnell et al., 2008), while we estimate the demand through an equation derived from the median voter theorem model. Using 2010 data, we find evidence that efficient management of spending is sufficient to meet excess demand for goods and services in the health sector. – – O objetivo deste artigo é avaliar se é necessário aumentar os recursos disponíveis para os governos locais, ou se o melhor uso desses recursos é suficiente. Esse estudo contribui à literatura, tanto na oferta quanto na demanda de serviços públicos em saúde. Se a demanda é estimada corretamente, é possível comparar o valor previsto da demanda com o gasto efetivamente realizado em saúde. Se o gasto efetivamente realizado é menor do que o gasto demandado, n\~ao haverá, a princípio, necessidade de gastos adicionais. Se os escores de eficiência (ladoda oferta) indicarem que os governos locais podem simplesmente “economizar” recursos para compensar a diferença, ent\~ao é possível reduzir (ou trazer a zero) novos recursos apenas exigindo que os governos locais gerenciem eficientemente suas despesas. Uma vez que os municípios no Brasil s\~ao muito heterogêneos, estimamos sua eficiência usando a abordagem de metafronteira (O'Donnell et al., 2008), enquanto estimamos a demanda através de uma equaç\~ao derivada do modelo do teorema do eleitor mediano. Usando dados de 2010, encontramos evidências de que uma gest\~ao eficiente dos gastos é suficiente para atender à demanda excessiva de bens e serviços no setor de saúde.
Keywords: C31; D24; I12; H72; 330; Health; Municipalities; Metafrontier; Data envelopment analysis; Median voter; Quantile regression